2022
DOI: 10.1371/journal.pone.0264218
|View full text |Cite
|
Sign up to set email alerts
|

Association of stigma with mental health and quality of life among Indonesian COVID-19 survivors

Abstract: Background and objective Coronavirus disease 2019 (COVID-19) survivors face societal stigma. The study aims to analyze the association of this stigma with the mental health and quality of life of COVID-19 survivors. Methods In this cross-sectional study, we observed 547 adults who were previously documented as severe acute respiratory syndrome coronavirus (SARS-CoV-2) positive by a polymerase chain reaction (PCR) test, treated in a hospital or an emergency hospital and proven to be SARS-CoV-2 negative by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 40 publications
4
30
1
2
Order By: Relevance
“…In previous studies, the prevalence ranged from 29.4-84.5% in survivor-reported studies [4,6,[25][26][27] and 45.9% − 64% in public-reported study [12,24,25]. Therefore, the value of 51.8% reported in this study still fell within the former range.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In previous studies, the prevalence ranged from 29.4-84.5% in survivor-reported studies [4,6,[25][26][27] and 45.9% − 64% in public-reported study [12,24,25]. Therefore, the value of 51.8% reported in this study still fell within the former range.…”
Section: Discussionsupporting
confidence: 48%
“…Second, we compared our results with the study that classi ed stigma into levels. Among the survivor-reported studies, only the study by Wahyuhadi et al 4 presented the level of stigma. Wahyuhadi et al found that 83.55% of the survivors experienced moderate-to-high stigmatization, whereas, only 19.9% reported moderate-to-high levels of stigma in this study, Third, the comparison was made to studies within Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) declared COVID-19 a global pandemic in March 2020 [31,32]. This global pandemic has caused unparalleled ruffles for global economic and human life [33,34]. As a result, the world's global trade suffered much due to the COVID-19 pandemic in 2020, and the growth trend of the world economy expects to remain low compared with the pre-pandemic situation [35].…”
Section: Impact Of the Covid-19 Pandemic On The World Economymentioning
confidence: 99%
“…Mental health is a condition of emotional, psychological, social, and spiritual health where this condition can be seen in satisfying interpersonal relationships (1)(2)(3). World Health Organization (WHO) reported that around 35 million people were stressed, 60 million people were affected by bipolar disorder, 21 million people were affected by schizophrenia, and 47.5 million people were affected by dementia (4).…”
Section: Introductionmentioning
confidence: 99%